Empire's Violent End : Comparing Dutch, British, and French Wars of Decolonization, 1945–1962 - Luttikhuis, Bart; Brocades Zaalberg, Thijs (Book collections on Project MUSE., 2022)
"This book explores various aspects of empire's violent end. The comparative analyses, focused mainly on Dutch, French and British cases, all revolve around the central questions of why, how, and to what extent security forces in service of the colonial powers in so many of the decolonization wars ended up using extreme violence" --